Yakuza Masculinity: Marginalized Hegemonic in Gokusen Manga - Puspitasari, Diana; Suryadi, Yudi; Kumasaka, Hinano (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Masculinity is a construction formed by society because of the expectations of men in society, so various forms of masculinity emerge. The Yakuza group is a group that is very synonymous with masculinity and is even referred to as the world of men. However, in reality, their masculine form shackles them in social interaction. The purpose of this study is to describe the forms of Yakuza masculinity so that there will be visible differences in the forms of masculinity between Yakuza and society in general. Yakuza masculinity has a general concept of masculinity, or is called hegemonic masculinity. However, forms of masculinity that are too extreme make their masculinity marginal. That happens because of differences in the interpretation of masculinity by society toward certain groups. The data is from images and dialogues representing Yakuza forms of masculinity in Gokusen manga. Data collection used a literature review technique, and data analysis used a qualitative descriptive technique.  The findings suggest that masculinity owned by the Yakuza group represents a form of hegemonic masculinity, but the form of masculinity becomes a problem for its existence. The form of masculinity has a dual identity as a tool of legitimacy and a means of subordination to individuals and groupsKeywords: Hegemonic, Marginal Masculinity, Masculinity, Yakuza Masculinity, Yakuza